Pyridine dicarboxylic acid-containing self-assembled hole transport material, synthesis method and application as optoelectronic device
Patent Information
- Application Number
- CN202311756903.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-19
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-12-19
AI Technical Summary
但是目前发展的具有锚定基团的有机小分子空穴传输材料面临着稳定性较差以及器件性能不佳等问题
[0032](1)吡啶羧基的引入,大幅度提高有机空穴传输材料的稳定性,包括光稳定性、热稳定性、氧化还原稳定性等,有益于器件工作状态下的长期稳定。
Smart Images

Figure CN117603135B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organic semiconductor technology, specifically relating to a self-assembled hole transport material containing pyridine dicarboxylic acid, its synthesis method, and its application. Background Technology
[0002] Organic semiconductor materials have attracted widespread attention from industry, academia, and research institutions due to their unique advantages, including solution processability, low cost, simple synthesis, diverse structures / types, tunable performance, and ease of fabrication into large-area and flexible optoelectronic devices. They show broad application prospects in next-generation high-performance, ultra-low-cost photovoltaic power generation, flat panel displays, biosensors, and flexible wearable devices. The global semiconductor industry is expected to gradually recover in 2024, re-entering a period of steady growth. According to forecasts from global market research institutions such as Gartner, IDC, and WSTS, the global semiconductor industry is projected to grow at double-digit rates in 2024, with an average predicted growth rate of around 13%-15%, exceeding $600 billion in market size. Organic hole transport materials, as a crucial component of novel optoelectronic devices, play a vital role in the collection and transport of holes and the blocking of electrons, significantly impacting the photoelectric conversion efficiency and stability of the devices.
[0003] In recent years, self-assembled single-molecule (SAM) hole transport materials have gained significant attention due to their low raw material costs, simple synthesis routes, well-defined molecular structures, ability to be processed using green alcohol solvents, strong adhesion to substrates, good solvent resistance, and ease of energy level adjustment through chemical modification. In particular, their molecular self-assembly method allows for the flexible and efficient fabrication of samples with controllable surface properties and shapes. Self-assembly can occur in solution or on solid surfaces, with molecules or particles aggregating at the interface to adjust the structure and ultimately form a stable thin film. Therefore, self-assembled hole transport materials play a crucial role in optoelectronics. The preparation of hole transport layers using small organic molecules containing anchoring groups has been shown to possess excellent charge selectivity (EnergyEnviron.Sci., 2019, 12, 230-237). However, currently developed small organic molecule hole transport materials with anchoring groups face challenges such as poor stability and unsatisfactory device performance. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a self-assembled monolayer hole transport material with good hole transport performance, strong interface passivation capability, and suitable for large-scale applications.
[0005] To achieve the above objectives, the present invention provides a hole transport material containing pyridine dicarboxylic acid groups, having the following general chemical formula (I):
[0006]
[0007] In the formula, R1-R2 are independently selected from any one or two of hydrogen, halogen, alkoxy, thioalkoxy, trifluoromethyl, and C1-C6 alkyl, and R l -R2 can represent different substitution positions or different numbers of substitutions; L represents single bond, phenyl, thiophene, furan, biphenyl; X represents empty, single bond, oxygen, sulfur, carbonyl, sulfonyl, carbodimethyl, nitromethyl, silyldimethyl.
[0008] Furthermore, formula (I) is any one of the following compounds i to viii:
[0009]
[0010] Wherein, the substituents R1 and R2 are independently any one or two of -H, -F, -Cl, -Br, -I, -OCH3, -SCH3, -CH3, -CH2CH3, and -CF3, and R l R2 can be different substitution positions or different substitution numbers; L represents a single bond, phenyl, thiophene, furan, or biphenyl.
[0011] Furthermore, the substituents R1 and R2 are -H or -OCH3, and R l R2 is in the same para-substitution position as R2; L is a single bond, phenyl.
[0012] The present invention discloses a method for synthesizing a pyridine dicarboxylic acid self-assembled hole transport material, comprising:
[0013] S1. The step of preparing intermediate 1 involves chlorinating 4-hydroxypyridine-2,6-dicarboxylic acid with phosphorus oxychloride and then esterifying it with tert-butanol (TBA) in a mixed solution of 4-dimethylaminopyridine (DMAP) and dichloromethane (DCM).
[0014]
[0015] S2. Intermediate 1 is coupled with an aromatic amine compound in a mixed solution of tetrahydrofuran (THF) and sodium hydride (NaH), followed by hydrolysis in a hydrochloric acid system to prepare a hole transport material containing pyridine dicarboxyl groups.
[0016]
[0017] Furthermore, in step (S1), the molar ratio of 4-hydroxypyridine-2,6-dicarboxylic acid, phosphorus oxychloride, tert-butanol and 4-dimethylaminopyridine is 1:2~3:2~3:0.05~0.1; the esterification reaction temperature is 80~100℃, and the esterification reaction time is 12~24h.
[0018] Furthermore, in step (S2), the molar ratio of intermediate 1, aromatic amine compound and sodium hydride is 1:1 to 1.5:1 to 1.2; the coupling reaction temperature is 40 to 50°C, and the coupling reaction time is 24 to 48 h.
[0019] The present invention discloses a method for synthesizing a pyridine dicarboxylic acid self-assembled hole transport material, comprising:
[0020] (a) The step of preparing intermediate 1 by chlorinating 4-hydroxypyridine-2,6-dicarboxylic acid with phosphorus oxychloride and then esterifying it with tert-butanol (TBA) in a mixed solution of 4-dimethylaminopyridine (DMAP) and dichloromethane (DCM).
[0021]
[0022] (b) The step of preparing intermediate 2 by catalytic coupling reaction of intermediate 1 and pinacol diboronate in a mixed solution of potassium acetate and tetrahydrofuran (THF) via tris(dibenzylacetone)palladium and 2-dicyclohexylphosphine-2′,4′,6′-triisopropylbiphenyl.
[0023]
[0024] (c) The step of preparing a hole transport material containing a pyridine dicarboxylic acid group by catalytic coupling reaction of intermediate 2 and a bromoaromatic hydrocarbon in a mixed solution of potassium phosphate and tetrahydrofuran via palladium acetate and X-phos.
[0025]
[0026] Furthermore, in step (a), the molar ratio of 4-hydroxypyridine-2,6-dicarboxylic acid, phosphorus oxychloride, tert-butanol and 4-dimethylaminopyridine is 1:2~3:2~3:0.05~0.1; the esterification reaction temperature is 80~100℃, and the esterification reaction time is 12~24h.
[0027] Furthermore, in step (b), the molar ratio of intermediate 1, pinacol diborate, potassium acetate, tris(dibenzylacetone)palladium, and 2-dicyclohexylphosphine-2′,4′,6′-triisopropylbiphenyl is 1:1–1.5:1–3:0.02–0.03:0.04–0.06; the coupling reaction temperature is 50–60 °C, and the coupling reaction time is 8–12 h.
[0028] Furthermore, in step (c), the molar ratio of intermediate 2, bromoaromatic hydrocarbon, potassium phosphate, palladium acetate, and 2-dicyclohexylphospho-2′,4′,6′-triisopropylbiphenyl is 1:1–1.5:1–3:0.02–0.03:0.04–0.06; the coupling reaction temperature is 50–60 °C, and the coupling reaction time is 12–24 h.
[0029] Another object of the present invention is for the application of optoelectronic devices, wherein the optoelectronic device comprises at least a transparent conductive oxide substrate, a hole transport layer, a light absorption layer, an electron transport layer and an electrode layer arranged sequentially; or, comprises a transparent conductive oxide substrate, a hole transport layer, a light emission layer, an electron transport layer and an electrode layer arranged sequentially; wherein, a metal back electrode is disposed on the transparent conductive oxide electrode layer; and the hole transport layer is the above-mentioned self-assembled hole transport material containing pyridine dicarboxyl groups as shown in general formula (I).
[0030] Optionally, the organic hole transport layer is obtained by dissolving a self-assembled hole transport material containing pyridine dicarboxylic acid as shown in general formula (I) in an alcohol solvent to prepare a solution with a concentration of 1 to 10 mg / mL, and then coating it onto a transparent conductive oxide substrate.
[0031] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0032] (1) The introduction of pyridine carboxyl groups greatly improves the stability of organic hole transport materials, including photostability, thermal stability, redox stability, etc., which is beneficial to the long-term stability of the device under working conditions.
[0033] (2) The introduction of pyridine carboxyl groups can adjust the frontier orbital energy level of the material, making it more compatible with the energy level of the active layer material, thereby improving the efficiency of interfacial carrier injection and extraction and enhancing device performance.
[0034] (3) The introduction of pyridine carboxyl groups can passivate the structural defects at the interface, prolong the carrier lifetime in the active layer, and improve the open-circuit voltage and fill factor of optoelectronic devices.
[0035] (4) The introduction of pyridine carboxyl groups can reduce the erosion of the active layer by water and reduce the diffusion of components in the active layer due to the hydrophobicity of pyridine carboxyl groups. Both of these aspects help to improve the stability of optoelectronic devices and extend the battery life. Attached Figure Description
[0036] Figure 1 This is a schematic diagram of the optoelectronic device structure of the present invention;
[0037] Figure 2 J / V curves of perovskite solar cells prepared using compounds 1-3 provided in this invention as hole transport materials;
[0038] Figure 3 J / V curves of perovskite solar cells prepared using compounds 4-6 provided in this invention as hole transport materials;
[0039] Figure 4J / V curves of perovskite solar cells prepared using compounds 7-9 provided in this invention as hole transport materials;
[0040] Figure 5 J / V curves of perovskite solar cells prepared using compounds 10-12 provided in this invention as hole transport materials;
[0041] Figure 6 J / V curves of perovskite solar cells prepared using compounds 13-15 provided in this invention as hole transport materials;
[0042] Figure 7 J / V curves of perovskite solar cells prepared using compounds 16-18 provided in this invention as hole transport materials;
[0043] Figure 8 J / V curves of perovskite solar cells prepared using compounds 19-20 provided in this invention as hole transport materials;
[0044] Figure 9 The graph shows the current density and brightness of perovskite light-emitting diodes prepared using compounds 1-3 provided in this invention as hole transport materials as voltage.
[0045] Figure 10 The graph shows the current density and brightness of perovskite light-emitting diodes prepared using compounds 4-6 provided in this invention as hole transport materials as voltage.
[0046] Figure 11 The graph shows the current density and brightness of perovskite light-emitting diodes prepared using compounds 7-9 provided in this invention as hole transport materials as voltage.
[0047] Figure 12 The graph shows the current density and brightness of perovskite light-emitting diodes prepared using compounds 10-12 provided in this invention as hole transport materials as voltage.
[0048] Figure 13 The graph shows the current density and brightness of perovskite light-emitting diodes prepared using compounds 13-15 provided in this invention as hole transport materials as voltage.
[0049] Figure 14 The graph shows the current density and brightness of perovskite light-emitting diodes prepared using compounds 16-18 provided in this invention as hole transport materials as voltage.
[0050] Figure 15 The graph shows the current density and brightness of perovskite light-emitting diodes prepared using compounds 19-20 provided in this invention as hole transport materials as a function of voltage. Detailed Implementation
[0051] To further illustrate the technical means and effects adopted by the present invention to achieve the intended purpose, the specific embodiments, structures, features, and effects of the present invention will be described in detail below with reference to the accompanying drawings and preferred embodiments. More specifically, the compounds in the examples are selected from the following structures:
[0052]
[0053]
[0054]
[0055] Example 1
[0056] Synthesis of Compound 1
[0057]
[0058] (1) Synthesis of intermediate 1:
[0059]
[0060] Weigh SM1 (48g, 1.0eq) and add it to a 500mL three-necked flask. Add 200mL of POCl3 and connect it to a tail gas treatment device. Absorb the acidic tail gas with an aqueous solution of NaOH. Heat to 100℃ and reflux with stirring for about 10h. Stop the reaction. Rotate off the remaining POCl3. Add tert-butanol (40mL), DMAP (10g), 20mL of ultra-dry DCM, and 10mL of pyridine to a 500mL flask and stir well. Dilute the concentrated solution from the previous step with 50mL of ultra-dry DCM and transfer it to a constant pressure dropping funnel. Slowly add the solution dropwise to the flask. After stirring for about 12h, concentrate the reaction solution and separate by column chromatography. A total of 42.68g of white solid product was obtained, with a yield of 57.6%. 1 H NMR(400MHz,DMSO-d6)δ7.38(s,2H),0.86(s,18H).HRMS(ESI,m / z):[M+H] + Calculated for C 15 H 21 ClNO4,314.1159,found 314.1168.
[0061] (2) Synthesis of Compound 1:
[0062]
[0063] Weigh SM2 (0.30 g, 1.0 eq), intermediate 1 (0.62 g, 1.1 eq), and NaH (0.22 g, 5.0 eq), add them to a 50 mL three-necked flask, add ultra-dry THF (20 mL), and heat to 50 °C. After stirring for 24 h, proceed to the next step. Slowly add 5 mL of purified water to the reaction solution and hydrolyze under alkaline conditions, stirring for about 12 h. A large amount of solid product precipitates in the reaction solution. Concentrate the reaction solution, remove a small amount of THF by evaporation, filter, and dry to obtain a yellow solid. Dissolve the solid in a large amount of ethanol, filter to remove impurities insoluble in ethanol, concentrate the ethanol, filter again to obtain the product, dry to obtain 130 mg of yellow solid, yield 22.0%. 1 H NMR(400MHz,Chloroform-d)δ7.55(s,2H),7.32-7.25(m,4H),7.14-7.08(m,4H),7.04(tt,J=7.7,1.4Hz,2H).HRMS(ESI,m / z):[M+H] + Calculated for C 19 H 13 N2O4,333.0875,found333.0816.
[0064] Example 2
[0065] Synthesis of Compound 2
[0066]
[0067] (1) Synthesis of intermediate 1: Same as the synthesis of intermediate 1 in Example 1, with a yield of 57.6%. 1 H NMR (400MHz, DMSO-d6) δ7.38 (s, 2H), 0.86 (s, 18H).
[0068] (2) Synthesis of intermediate 2:
[0069]
[0070] Weigh intermediate 1 (5.0 g, 1.0 eq), pinacol diborate (4.87 g, 1.2 eq), potassium acetate (4.69 g, 3.0 eq), Pd2(dba)3 (0.15 g), and X-phos (0.30 g) and dissolve them in 50 mL of ultra-dry THF. Stir at 60 °C under argon protection. After stirring for about 10 h, the reaction is complete. Filter the reaction solution, remove salts, and concentrate the reaction solution to about 10 mL. Stir for about 30 min, and a large amount of product precipitates. Filter, wash with petroleum ether, and dry to obtain 6.59 g of white solid product, yield 65.4%. 1H NMR(400MHz,DMSO-d6)δ7.38(s,2H),0.86(s,30H).HRMS(ESI,m / z):[M+H] + Calculated for C 21 H 32 BNO6,405.2323,found 405.2349.
[0071] (3) Synthesis of intermediate 3:
[0072]
[0073] Weigh SM3 (0.30 g, 1 eq), intermediate 2 (0.45 g, 1.2 eq), and NaH (0.60 g, 3 eq), add them to a 50 mL three-necked flask, add THF (20 mL) and water (5 mL), and heat to 50 °C; stir overnight, evaporate to dryness, and separate by column chromatography (PE:EA = 8:1) to obtain a yellow product; dry to obtain 0.36 g, yield 75%. 1 H NMR(400MHz,Chloroform-d)δ8.20(s,2H),7.63-7.57(m,2H),7.31-7.26(m,4H),7.21-7.18 (m,2H),7.13-7.08(m,4H),7.04(tt,J=7.7,1.4Hz,2H),1.56(s,18H).HRMS(ESI,m / z):[M+H] + Calculated for C 33 H 34 N2O4,522.2519, found 522.2589.
[0074] (4) Synthesis of compound 2:
[0075]
[0076] Weigh intermediate 3 (0.11 g, 0.21 mmol), add 20 mL THF and 10 mL water, stir for 12 h to hydrolyze the ester, and perform TLC. Hydrolysis is complete. Add concentrated hydrochloric acid to adjust the pH to 2. No precipitate forms. Concentrate the reaction solution to about 10 mL of water. Precipitate forms. After filtration, wash the product repeatedly with water. Dry to obtain 73 mg of product, yield 84.8%. 1H NMR(400MHz,Chloroform-d)δ8.28(s,2H),7.64-7.58(m,2H),7.32-7.25(m,4H),7 .22-7.16(m,2H),7.11(d,J=1.3Hz,1H),7.11-7.00(m,5H).HRMS(ESI,m / z):[M+H] + Calculated for C 25 H 18 N2O4,410.1267,found 410.1217.
[0077] Example 3
[0078] Synthesis of compound 3:
[0079]
[0080] The synthesis of compound 3 was similar to that of compound 2, yielding 156 mg of product with a yield of 74.6%. 1 H NMR(400MHz,Chloroform-d)δ8.28(s,2H),7.64-7.58(m,2H),7.22-7.16(m,2H),7.14-7.09(m,4H),6.95-6.89(m,4H),3.79(s,6H).HRMS(ESI,m / z):[M+H] + Calculated for C 27 H 23 N2O6,471.1556, found 471.1594.
[0081] Example 4
[0082] Synthesis of compound 4:
[0083]
[0084] The synthesis of compound 4 was similar to that of compound 2, yielding 215 mg of product, with a yield of 81.4%. 1 H NMR(400MHz,Chloroform-d)δ8.29(s,2H),8.16-8.11(m,2H),7.72-7.68(m,2H),7.68-7 .59(m,4H),7.35(ddd,J=7.5,6.1,1.3Hz,1H),7.33-7.27(m,3H).HRMS(ESI,m / z):[M+H] + Calculated for C 25 H17 N2O4,409.1188,found 409.1113.
[0085] Example 5
[0086] Synthesis of compound 5:
[0087]
[0088] The synthesis of compound 5 was similar to that of compound 1, yielding 109 mg of product, with a yield of 41.6%. 1 H NMR(400MHz,Chloroform-d)δ8.99(s,2H),7.89(d,J=2.7Hz,1H),7.66(d,J=1.8Hz,1H),7.29 (dd,J=8.1,2.6Hz,2H),6.93(ddd,J=9.5,8.0,2.4Hz,2H),3.83(s,6H).HRMS(ESI,m / z):[M+H] + Calculated for C 21 H 17 N2O6,393.1087, found 393.1027.
[0089] Example 6
[0090] Synthesis of compound 6:
[0091]
[0092] The synthesis of compound 6 was similar to that of compound 2, yielding 315 mg of product in 86.1% yield. 1 H NMR(400MHz,Chloroform-d)δ8.29(s,2H),7.89(d,J=2.8Hz,1H),7.73-7.59(m,5H),7.3 6(t,J=8.0Hz,2H),6.92(ddd,J=9.5,8.1,2.4Hz,2H),3.83(s,6H).HRMS(ESI,m / z):[M+H] + Calculated for C 27 H 21 N2O6,469.1400,found 469.1413.
[0093] Example 7
[0094] Synthesis of compound 7:
[0095]
[0096] The synthesis of compound 7 was similar to that of compound 1, yielding 136 mg of product, with a yield of 51.6%. 1 H NMR(400MHz,Chloroform-d)δ7.86(s,2H),7.19(dd,J=7.3,1.7Hz,2H),7.09(td,J=7.3,1 .5Hz,2H),7.08(td,J=7.4,1.5Hz,2H),6.73(dd,J=7.4,1.6Hz,2H).HRMS(ESI,m / z):[M+H] + Calculated for C 19 H 12 N2O5,348.0746,found 348.0728.
[0097] Example 8
[0098] Synthesis of compound 8:
[0099]
[0100] The synthesis of compound 8 was similar to that of compound 1, yielding 105 mg of product in 46.8% yield. 1 H NMR(400MHz,Chloroform-d)δ7.84(s,2H),7.30(dd,J=7.3,1.4Hz,2H),7.27-7.20(m,4H),7.13(ddd,J=7.5,6.6,2.4Hz,2H).HRMS(ESI,m / z):[M+H] + Calculated for C 19 H 12 N2O4S,364.0518,found 364.0573.
[0101] Example 9
[0102] Synthesis of compound 9:
[0103]
[0104] The synthesis of compound 9 was similar to that of compound 1, yielding 142 mg of product, with a yield of 41.2%. 1H NMR(400MHz,Chloroform-d)δ8.02(dd,J=7.6,1.5Hz,2H),7.85(s,2H),7.39(td,J=7.4,1 .5Hz,2H),7.29(dd,J=7.5,1.6Hz,2H),7.08(td,J=7.5,1.6Hz,2H).HRMS(ESI,m / z):[M+H] + Calculated for C 20 H 12 N2O5,360.0746,found 360.0729.
[0105] Example 10
[0106] Synthesis of compound 10:
[0107]
[0108] The synthesis of compound 10 was similar to that of compound 1, yielding 212 mg of product, with a yield of 51.9%. 1 H NMR(400MHz,Chloroform-d)δ7.88-7.83(m,2H),7.51(td,J=7.4,1.7Hz,4H),7.41-7.30(m,2H).HRMS(ESI,m / z):[M+H] + Calculated for C 19 H 12 N2O6S,396.0416,found 396.0490.
[0109] Example 11
[0110] Synthesis of compound 11:
[0111]
[0112] The synthesis of compound 11 was similar to that of compound 1, yielding 115 mg of product with a yield of 47.9%. 1 H NMR (400MHz, Chloroform-d) δ7.85 (s, 2H), 7.17 (ddd, J=19.6, 7.4, 1.5Hz, 6H), 7.07 (td, J=7.4, 1.7Hz, 2H), 1.54 (s, 6H). HRMS (ESI, m / z): [M+H] + Calculated for C 22 H 18N2O4,374.1267, found 374.1217.
[0113] Example 12
[0114] Synthesis of compound 12:
[0115]
[0116] The synthesis of compound 12 was similar to that of compound 1, yielding 141 mg of product, with a yield of 43.8%. 1 H NMR (400MHz, Chloroform-d) δ7.84 (s, 2H), 7.17-7.09 (m, 4H), 7.06 (dd, J=7.8, 1.1Hz, 2H), 6.99-6.91 (m, 2H), 3.41 (s, 3H). HRMS (ESI, m / z): [M+H] + Calculated for C 20 H 15 N3O4,361.1063,found 361.1002.
[0117] Example 13
[0118] Synthesis of compound 13:
[0119]
[0120] The synthesis of compound 13 was similar to that of compound 1, yielding 115 mg of product, with a yield of 39.4%. 1 H NMR(400MHz,Chloroform-d)δ7.86(s,2H),7.48-7.40(m,2H),7.36-7.27(m,4H),7.27-7.19(m,2H),1.44(s,6H).HRMS(ESI,m / z):[M+H] + Calculated for C 21 H 18 N2O4Si,390.1036, found390.1099.
[0121] Example 14
[0122] Synthesis of compound 14:
[0123]
[0124] The synthesis of compound 14 was similar to that of compound 2, yielding 215 mg of product, with a yield of 66.3%. 1H NMR(400MHz,Chloroform-d)δ8.15(s,2H),7.70-7.64(m,2H),7.33-7.27(m,2H) ,7.22-7.14(m,2H),7.11-7.03(m,4H),6.84-6.77(m,2H).HRMS(ESI,m / z):[M+H] + Calculated for C 25 H 16 N2O5,424.1059,found 424.1090.
[0125] Example 15
[0126] Synthesis of compound 15:
[0127]
[0128] The synthesis of compound 15 was similar to that of compound 2, yielding 175 mg of product in 63.8% yield. 1 H NMR(400MHz,Chloroform-d)δ8.15(s,2H),7.71-7.66(m,2H),7.29(dd,J=7.4,1 .3Hz,4H),7.26-7.18(m,4H),7.13(td,J=7.3,1.9Hz,2H).HRMS(ESI,m / z):[M+H] + Calculated for C 25 H 16 N2O4S,440.0831,found 440.0892.
[0129] Example 16
[0130] Synthesis of compound 16:
[0131]
[0132] The synthesis of compound 16 was similar to that of compound 2, yielding 118 mg of product in 68.1% yield. 1 H NMR(400MHz,Chloroform-d)δ8.10(s,2H),8.02(dd,J=7.6,1.5Hz,2H),7.71–7.66(m,2H),7.41(td,J=7.4,1 .4Hz,2H),7.32(dd,J=7.5,1.6Hz,2H),7.30–7.26(m,2H),7.09(td,J=7.4,1.5Hz,2H).HRMS(ESI,m / z):[M+H]+ Calculated for C 26 H 16 N2O5,436.1059,found436.1010.
[0133] Example 17
[0134] Synthesis of compound 17:
[0135]
[0136] The synthesis of compound 17 was similar to that of compound 2, yielding 331 mg of product with a yield of 79.5%. 1 H NMR(400MHz,Chloroform-d)δ8.10(s,2H),7.86(dd,J=7.5,1.3Hz,2H),7.72-7.66(m,2H) ,7.48(td,J=7.1,2.0Hz,2H),7.38-7.30(m,4H),7.30-7.25(m,2H).HRMS(ESI,m / z):[M+H] + Calculated for C 25 H 16 N2O6S,472.0729,found 472.0680.
[0137] Example 18
[0138] Synthesis of compound 18:
[0139]
[0140] The synthesis of compound 18 was similar to that of compound 2, yielding 266 mg of product, with a yield of 62.7%. 1 H NMR(400MHz,Chloroform-d)δ8.10(s,2H),7.72-7.66(m,2H),7.31-7.25(m,2H),7.2 1-7.14(m,4H),7.08(ddd,J=7.0,6.3,1.5Hz,4H),1.54(s,6H).HRMS(ESI,m / z):[M+H] + calculated for C 28 H 22 N2O4,450.1580,found 450.1521.
[0141] Example 19
[0142] Synthesis of compound 19:
[0143]
[0144] The synthesis of compound 19 was similar to that of compound 2, yielding 253 mg of product in 73.8% yield. 1 H NMR(400MHz,Chloroform-d)δ8.10(s,2H),7.71-7.66(m,2H),7.33-7.27(m,2H),7.14(ddd,J=7.5, 6.1,2.6Hz,2H),7.09(dd,J=7.1,1.1Hz,2H),7.01-6.93(m,4H),3.41(s,3H).HRMS(ESI,m / z):[M+H] + Calculated for C 26 H 19 N3O4,437.1376, found 437.1302.
[0145] Example 20
[0146] Synthesis of compound 20:
[0147]
[0148] The synthesis of compound 20 was similar to that of compound 2, yielding 310 mg of product in 78.3% yield. 1 H NMR(400MHz,Chloroform-d)δ8.10(s,2H),7.71-7.65(m,2H),7.47-7.40(m,2H),7.35-7.26(m,6H),7.23-7.15(m,2H),0.44(s,6H).HRMS(ESI,m / z):[M+H] + Calculated for C 27 H 22 N2O4Si,466.1349, found 466.1368.
[0149] The following analysis of the preparation process and performance testing of perovskite solar cell devices A1 to A20 and perovskite light-emitting diode devices B1 to B20 prepared with the compounds of the present invention further details the uses and effects of the compounds of the present invention.
[0150] Application Example 1
[0151] The fabrication method of the A1 perovskite solar cell is as follows:
[0152] 1) Cleaning of the ITO conductive glass substrate;
[0153] 2) Preparation of hole transport layer (HTL): Compound 1 was dissolved in ethanol solvent, spin-coated on ITO, and then annealed at 120℃ for 20 min to remove adsorbed water molecules for later use.
[0154] 3) Preparation of perovskite thin film (perovskite layer): The solubility of the perovskite precursor solution was 1.2 M. The perovskite thin film was prepared by a one-step anti-solvent method. Spin coating was performed in two stages, with the first stage at a speed of 1000 rpm. -1 Spin coating for 10 seconds, with an acceleration of 200 rpm. -2 The second stage is 5000 rpm. -1 Apply for 30 seconds, with an acceleration of 2000 rpm. -2 20 seconds before the end of the second stage, 600 μL of toluene was added as an antisolvent to the center of the perovskite film, and finally heated at 100°C for 30 minutes to obtain the final perovskite film.
[0155] 3) Preparation of electron transport layer (ETL) and hole blocking layer: A solution of PCBM with a concentration of 20 mg / mL was prepared using chlorobenzene. -1 Two-step spin coating process (800 rpm) -1 10s; 4000 rpm -1 Anneal at 80℃ for 10 minutes (30s).
[0156] 4) Hole blocking layer preparation: Finally, a hole blocking layer (ITO) was prepared by drop-coating 120 μL of BCP isopropanol solution.
[0157] 5) Back electrode preparation: using a vacuum evaporation apparatus (<5×10⁻⁶) -4 The negative electrode is formed by evaporating 100nm of silver (Pa).
[0158] The fabrication method and process of device A2 are the same as those of device A1, except that the hole transport material (compound 2) layer provided by this invention is prepared on ITO.
[0159] The fabrication method and process of device A3 are the same as those of device A1, except that the hole transport material (compound 3) layer provided by this invention is prepared on ITO.
[0160] The fabrication method and process of device A4 are the same as those of device A1, except that the hole transport material (compound 4) layer provided by this invention is prepared on ITO.
[0161] The fabrication method and process of device A5 are the same as those of device A1, except that the hole transport material (compound 5) layer provided by this invention is prepared on ITO.
[0162] The fabrication method and process of device A6 are the same as those of device A1, except that the hole transport material (compound 6) layer provided by this invention is prepared on ITO.
[0163] The fabrication method and process of device A7 are the same as those of device A1, except that the hole transport material (compound 7) layer provided by this invention is prepared on ITO.
[0164] The fabrication method and process of device A8 are the same as those of device A1, except that the hole transport material (compound 8) layer provided by this invention is prepared on ITO.
[0165] The fabrication method and process of device A9 are the same as those of device A1, except that a hole transport material (compound 9) layer provided by the present invention is prepared on ITO.
[0166] The fabrication method and process of device A10 are the same as those of device A1, except that a hole transport material (compound 10) layer provided by the present invention is prepared on ITO.
[0167] The fabrication method and process of device A11 are the same as those of device A1, except that the hole transport material (compound 11) layer provided by this invention is prepared on ITO.
[0168] The fabrication method and process of device A12 are the same as those of device A1, except that the hole transport material (compound 12) layer provided by this invention is prepared on ITO.
[0169] The fabrication method and process of device A13 are the same as those of device A1, except that the hole transport material (compound 13) layer provided by this invention is prepared on ITO.
[0170] The fabrication method and process of device A14 are the same as those of device A1, except that the hole transport material (compound 14) layer provided by this invention is prepared on ITO.
[0171] The fabrication method and process of device A15 are the same as those of device A1, except that the hole transport material (compound 15) layer provided by this invention is prepared on ITO.
[0172] The fabrication method and process of device A16 are the same as those of device A1, except that a hole transport material (compound 16) layer provided by the present invention is prepared on ITO.
[0173] The fabrication method and process of device A17 are the same as those of device A1, except that the hole transport material (compound 17) layer provided by this invention is prepared on ITO.
[0174] The fabrication method and process of device A18 are the same as those of device A1, except that a hole transport material (compound 18) layer provided by the present invention is prepared on ITO.
[0175] The fabrication method and process of device A19 are the same as those of device A1, except that a hole transport material (compound 19) layer provided by the present invention is prepared on ITO.
[0176] The fabrication method and process of device A20 are the same as those of device A1, except that a hole transport material (compound 20) layer provided by the present invention is prepared on ITO.
[0177] Application Comparison Example 1
[0178] The fabrication method and process are the same as those for device A1, except that the hole transport material fabricated on ITO is Ref, and the structural formula of Ref is as follows:
[0179]
[0180] Perovskite solar cell performance testing: The current-voltage characteristic curve (IV) of the solar cell was recorded using a Keithley 2400 digital source meter, with a xenon lamp (Osram XBO 450) simulating AM 1.5 sunlight at an intensity of 1000 W / m². 2 After calibration with silicon cells, the test temperature was 25℃. The incident photon-to-electron coverage efficiency (IPCE), also known as external quantum efficiency (EQE), was measured using an Oriel-74125 system with a 300W xenon lamp (ILC Technology, USA) as the light source and a modulation frequency of 2Hz. The JV data of the tested cells are shown in Table 1 and... Figures 1-8 As shown.
[0181] Stability test of perovskite solar cells: After the prepared perovskite solar cell device was placed under conditions of 85% relative humidity (RH) and 50℃ for 240h, the relative values of its photoelectric conversion efficiency compared with the original efficiency are shown in Table 1.
[0182] Table 1
[0183]
[0184]
[0185] From Table 1 and Figures 2-8 It can be seen that: (1) When the pyridine carboxyl compound of the present invention is used as a hole transport material in a perovskite solar cell, the short-circuit density of the cell is greater than 14 mA / cm². -2The open-circuit voltage is greater than 1.10V, and the filler factor is greater than 73%. The photoelectric conversion efficiency under simulated sunlight intensity of 1.5AM is greater than 13%, with the highest reaching 17.45%. Compared with the reference compound, it shows a higher photoelectric conversion efficiency. This is mainly due to the introduction of the transport unit and pyridine carboxyl group, which adjusts the frontier orbital energy level of the material, making it more matched with the energy level of the active layer material, improving the interface carrier injection and extraction efficiency, and improving the device efficiency. In addition, it can passivate the structural defects of the interface, prolong the carrier lifetime in the perovskite active layer, and improve the open-circuit voltage and fill factor of the perovskite battery. (2) Due to the introduction of the transport unit and pyridine carboxyl group, the photostability and redox stability of the hole transport material can be improved. As can be seen from Table 1, after being placed under high temperature and high humidity for 240 hours, the perovskite battery using the compound of the present invention as the hole transport material still has good photoelectric conversion efficiency. Compared with the original value, it is higher than 80%, while the reference device is only 45%, showing the good stability of the battery of the present invention. In addition to increasing the stability of the material, the transmission unit can also increase the hydrophobicity of the material, reduce the erosion of the perovskite layer by moisture in the air during the operation of the perovskite battery, and improve the battery's lifespan.
[0186] Application Example 2
[0187] The fabrication method of the B1 perovskite light-emitting diode device is as follows:
[0188] 1) ITO anode: The ITO (indium tin oxide) glass substrate with a coating thickness of 150nm was wiped with ethanol, then cleaned twice with acetone, ultrasonically cleaned for 20min, and then transferred to an isothermal stage for drying. After baking, it was cooled and transferred to UV-O3 treatment for 15min.
[0189] 2) Preparation of hole transport layer (HTL): Compound 9 was dissolved in ethanol solvent, spin-coated onto ITO, and then annealed at 120℃ for 20 min to remove adsorbed water molecules for later use.
[0190] 3) Perovskite quantum dots were spin-coated onto the transport layer at 2000 rpm / 45 s with an acceleration of 1000. A 45 nm TPBi layer was deposited as the electron transport layer using a vacuum evaporation apparatus. A 100 nm Al layer was then vacuum-deposited on the electron injection layer as the back electrode.
[0191] The fabrication method and process of device B2 are the same as those of device B1, except that the hole transport material (compound 2) layer provided by this invention is prepared on ITO.
[0192] The fabrication method and process of device B3 are the same as those of device B1, except that the hole transport material (compound 3) layer provided by this invention is prepared on ITO.
[0193] The fabrication method and process of device B4 are the same as those of device B1, except that the hole transport material (compound 4) layer provided by this invention is prepared on ITO.
[0194] The fabrication method and process of device B5 are the same as those of device B1, except that the hole transport material (compound 5) layer provided by this invention is prepared on ITO.
[0195] The fabrication method and process of device B6 are the same as those of device B1, except that a hole transport material (compound 6) layer provided by the present invention is prepared on ITO.
[0196] The fabrication method and process of device B7 are the same as those of device B1, except that the hole transport material (compound 7) layer provided by this invention is prepared on ITO.
[0197] The fabrication method and process of device B8 are the same as those of device B1, except that the hole transport material (compound 8) layer provided by this invention is prepared on ITO.
[0198] The fabrication method and process of device B9 are the same as those of device B1, except that the hole transport material (compound 9) layer provided by this invention is prepared on ITO.
[0199] The fabrication method and process of device B10 are the same as those of device B1, except that a hole transport material (compound 10) layer provided by the present invention is prepared on ITO.
[0200] The fabrication method and process of device B11 are the same as those of device B1, except that the hole transport material (compound 11) layer provided by this invention is prepared on ITO.
[0201] The fabrication method and process of device B12 are the same as those of device B1, except that the hole transport material (compound 12) layer provided by this invention is prepared on ITO.
[0202] The fabrication method and process of device B13 are the same as those of device B1, except that the hole transport material (compound 13) layer provided by this invention is prepared on ITO.
[0203] The fabrication method and process of device B14 are the same as those of device B1, except that the hole transport material (compound 14) layer provided by this invention is prepared on ITO.
[0204] The fabrication method and process of device B15 are the same as those of device B1, except that the hole transport material (compound 15) layer provided by this invention is prepared on ITO.
[0205] The fabrication method and process of device B16 are the same as those of device B1, except that a hole transport material (compound 16) layer provided by the present invention is prepared on ITO.
[0206] The fabrication method and process of device B17 are the same as those of device B1, except that the hole transport material (compound 17) layer provided by this invention is prepared on ITO.
[0207] The fabrication method and process of device B18 are the same as those of device B1, except that the hole transport material (compound 18) layer provided by this invention is prepared on ITO.
[0208] The fabrication method and process of device B19 are the same as those of device B1, except that the hole transport material (compound 19) layer provided by this invention is prepared on ITO.
[0209] The fabrication method and process of device B20 are the same as those of device B1, except that the hole transport material (compound 20) layer provided by this invention is prepared on ITO.
[0210] Application Comparison Example 2
[0211] The fabrication method and process are the same as those for device B1, except that the hole transport material fabricated on ITO is Ref, and the structural formula of Ref is as follows:
[0212]
[0213] The perovskite light-emitting device obtained above was subjected to IVL testing, and its relevant performance parameters are shown in Table 2.
[0214] Table 2
[0215]
[0216] From Table 2 and Figures 9-15 It can be seen that: (1) When the pyridine carboxyl compound of the present invention is used as a hole transport material in a perovskite light-emitting diode, the turn-on voltage is 2.6V and the luminous intensity is greater than 10000cd / m². 2 The external quantum efficiency is greater than 13%, and even reaches 15%. Due to the introduction of transport units and pyridine carboxyl groups, the frontier orbital energy level of the material is adjusted to better match the energy level of the active layer material, showing good interfacial carrier injection and extraction efficiency.
Claims
1. A hole transport material containing pyridine dicarboxylic acid groups, characterized in that, Having the general chemical structural formula shown in formula (I): (Ⅰ); In the formula, R1-R2 are independently selected from either hydrogen or methoxy; L represents a single bond or phenyl; X represents empty, single bond, oxygen, sulfur, carbonyl, sulfonyl, carbodimethyl, nitrogen-methyl, or silyldimethyl; and when L and X are both single bonds, R1-R2 are not hydrogen.
2. A method for synthesizing a hole transport material as described in claim 1, characterized in that, include: S1. The step of preparing intermediate 1 involves chlorinating 4-hydroxypyridine-2,6-dicarboxylic acid with phosphorus oxychloride and then esterifying it with tert-butanol in a mixed solution of 4-dimethylaminopyridine and dichloromethane. ; S2. Intermediate 1 is coupled with an aromatic amine compound in a mixed solution of tetrahydrofuran and sodium hydride, followed by hydrolysis in a hydrochloric acid system to prepare a hole transport material containing pyridine dicarboxyl groups. 。 3. The synthesis method as described in claim 2, characterized in that, In step (S1), the molar ratio of 4-hydroxypyridine-2,6-dicarboxylic acid, phosphorus oxychloride, tert-butanol, and 4-dimethylaminopyridine is 1:2~3:2~3:0.05~0.1; the esterification reaction temperature is 80~100℃, and the esterification reaction time is 12~24h; in step (S2), the molar ratio of intermediate 1, aromatic amine compound, and sodium hydride is 1:1~1.5:1~1.2; the coupling reaction temperature is 40~50℃, and the coupling reaction time is 24~48h.
4. A method for synthesizing a hole transport material as described in claim 1, characterized in that, include: (a) The step of preparing intermediate 1 by chlorinating 4-hydroxypyridine-2,6-dicarboxylic acid with phosphorus oxychloride and then esterifying it with tert-butanol in a mixed solution of 4-dimethylaminopyridine and dichloromethane. ; (b) The step of preparing intermediate 2 by catalytic coupling reaction of intermediate 1 and pinacol diborate in a mixed solution of potassium acetate and tetrahydrofuran via tris(dibenzylacetone)palladium and 2-dicyclohexylphosphine-2′,4′,6′-triisopropylbiphenyl. ; (c) The step of preparing a hole transport material containing pyridine dicarboxylic acid by catalytic coupling reaction of intermediate 2 and bromoaromatic hydrocarbon in a mixed solution of potassium phosphate and tetrahydrofuran via palladium acetate and X-phos. 。 5. The synthesis method as described in claim 3, characterized in that, In step (a), the molar ratio of 4-hydroxypyridine-2,6-dicarboxylic acid, phosphorus oxychloride, tert-butanol, and 4-dimethylaminopyridine is 1:2~3:2~3:0.05~0.1; the esterification reaction temperature is 80~100℃, and the esterification reaction time is 12~24h; in step (b), the molar ratio of intermediate 1, pinacol diboronate, potassium acetate, tris(dibenzylacetone)palladium, and 2-dicyclohexylphosphine-2′,4′,6′-triisopropylbiphenyl is 1:1~1.5: 1~3:0.02~0.03:0.04~0.06; the coupling reaction temperature is 50~60℃, and the coupling reaction time is 8~12h; in step (c), the molar ratio of intermediate 2, bromoaromatic hydrocarbon, potassium phosphate, palladium acetate and 2-dicyclohexylphospho-2′,4′,6′-triisopropylbiphenyl is 1:1~1.5:1~3:0.02~0.03:0.04~0.06; the coupling reaction temperature is 50~60℃, and the coupling reaction time is 12~24h.
6. The application of the hole transport material as described in claim 1 in the fabrication of the hole transport layer of an optoelectronic device.
7. An optoelectronic device, wherein the optoelectronic device comprises at least a transparent conductive oxide substrate, a hole transport layer, a light absorption layer, an electron transport layer, and an electrode layer sequentially disposed thereon; or, at least comprises a transparent conductive oxide substrate, a hole transport layer, a light-emitting layer, an electron transport layer, and an electrode layer sequentially disposed thereon, characterized in that, The hole transport layer contains the hole transport material as described in claim 1.
8. The optoelectronic device as described in claim 7, characterized in that, The hole transport layer is obtained by dissolving the hole transport material in an alcohol solvent to prepare a solution with a concentration of 1~10 mg / mL, and then coating it onto a transparent conductive oxide substrate.